Potential predictors of efficacy outcomes following tofacitinib dose reduction in patients with ulcerative colitis in stable remission: a post hoc analysis of outcomes from the RIVETING study - Joana Torres; Geert R. D’Haens; Miguel Regueiro; Genoile Santana; Julian Panés; Séverine Vermeire; Sean Gardiner; Nicole Kulisek; Irene Modesto; Chinyu Su; Nervin Lawendy; Rajiv Mundayat; et al. (Therapeutic Advances in Gastroenterology)
Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of ulcerative colitis (UC). Objectives: To investigate potential predictors of efficacy in RIVETING. Design: This post hoc analysis included patients with UC in stable remission (⩾6 months) on tofacitinib 10 mg twice daily (BID) maintenance therapy (⩾2 years of treatment), who received tofacitinib 5/10 mg BID in RIVETING. Methods: Achievement of modified Mayo (mMayo) remission, remission (based on total Mayo score), partial Mayo score (PMS) remission, and modified PMS (mPMS) remission at month (M)6 was analyzed by baseline characteristics, duration of PMS remission at RIVETING entry, biomarkers, and patient-reported outcomes (PROs) to identify factors associated with achieving/maintaining efficacy outcomes, including following dose reduction. Results: Seventy patients received tofacitinib 5 mg BID. At M6, PMS remission was maintained in 66.7%, 60.0%, 82.4%, 75.0%, and 90.0% of patients with baseline PMS remission durations of 6 to ⩽12, >12 to ⩽24, >24 to ⩽36, >36 to ⩽48, and >48 months, respectively. Patients in mMayo remission at M6 had smaller increases in PMS at M1 compared with those not in mMayo remission at M6, while numerically higher proportions of patients with a stool frequency subscore/rectal bleeding subscore/mPMS of 0 at M1/M3 achieved most efficacy endpoints at M6 compared with patients with respective subscores >0. Maintenance of mMayo remission was independent of the number of tumor necrosis factor inhibitors failed and/or prior corticosteroid use. In multivariable models (which included tofacitinib 10 mg BID data), endoscopic subscores (1 vs 0) at RIVETING baseline were significantly associated with lower odds of mMayo remission at M6 (odds ratio, 0.33; 95% confidence interval, 0.11–0.94; p  = 0.0379). Conclusion: Prior duration of remission/baseline endoscopic subscore may help guide tofacitinib dose reduction, while PROs may be useful early indicators of efficacy. Close monitoring of patients following dose reduction could identify those unlikely to achieve/maintain efficacy. Trial registration : ClinicalTrials.gov: NCT03281304.